Teachers' Perceptions of Discourse Usage in Elementary and Middle Grades Mathematics - Tuck, Beth A. (My University, 2018)
This dissertation is motivated by the research question “do years of teaching experience, educational status, and grade of instruction affect teachers' perceptions of univocal discourse usage, dialogic discourse usage, and general discourse usage”? This research is a survey design with foundations from Truxaw, Gorgievski, and DeFranco's (2008) instrument on classroom discourse usage. The goal of this study was to assess group differences in teachers' perceptions of univocal, dialogic, and general discourse, as well as differences due to the level of experience and education were explored. There were two statistically significant main effects for teaching experience as well as one statistically significant effect for grade band. For teaching experience and the dialogic discourse score, teachers with 11 or more years of experience had a mean dialogic discourse score (M = 35.85, SD = 5.30) that was significantly higher on average than teachers with 0 to 10 years of experience (M = 34.14, SD = 5.93). The mean of the elementary group (M = 34.78, SD = 5.65) was significantly lower than the mean of the middle grade level band group (M = 38.00, SD = 4.15). For teaching experience and the general discourse score, teachers with 11 or more years of experience had a mean general discourse score (M = 12.46, SD = 1.76) that was higher on average than teachers with 0 to 10 years of teaching experience (M = 11.83, SD = 2.05). The results and future research were discussed, and the findings support a need for further change centered on dialogic discourse.
Chapter I: INTRODUCTION 1 | Statement of the Problem 2 | The Gap in the Current Literature 3 | Purpose of the Study 4 | Original Contribution 4 | The Significance of the Study 5 | Advancing Theory 5 | Advances in Practice 7 | Background of the Study 8 | Conceptual Framework for the Study / Theoretical Foundation 11 | Research Questions 13 | Definition of Terms 13 | Procedures 17 | Limitations of the Study 18 | Organization of the Study 18 | Chapter II: REVIEW OF THE LITERATURE 19 | Concept Map with Explanation 21 | Conceptual Understanding of Discourse and Constructivism 21 | History of Discourse within the National Council of Teachers of Mathematics 28 | Discourse Defined 30 | Univocal Discourse versus Dialogic Discourse 34 | Discourse and Student Achievement 36 | Explanation versus Justification 37 | Discourse Outside of the United States 38 | Reform-Mathematics and Classroom Shifts 40 | Student-Centered Mathematics 45 | Mathematical Mindset 48 | The Inductive Model of Discourse 49 | Standards for Mathematical Practice 50 | Classroom Environment 52 | Learning Environment and Classroom Norms 54 | Student's Role in Discourse 55 | The Teacher's Role in Discourse 56 | Effective Questions 59 | Worthwhile Mathematical Tasks 60 | Chapter III: METHODS 64 | Research Design and Rationale 64 | Population, Participants, and Setting 65 | Sampling and Sampling Procedures 66 | Instrumentation and Operationalization of Constructs 67 | Validity and Reliability 68 | Content Validity 69 | Construct Validity 69 | Reliability 70 | Threats to Internal Validity 70 | Procedures 71 | Participation, Data Collection (Primary Data), and Management 72 | Data Analysis 73 | Descriptive Statistics 73 | Study Variables 74 | Ethical Procedures and Anticipated Ethical Issues in the Study 75 | Summary 76 | Chapter IV: RESEARCH FINDINGS 77 | Participants 77 | Instrumentation 78 | Study Variables 80 | Data Collection and Management 80 | Data Screening 81 | Results of Statistical Analyses 84 | Research Question 1 84 | Research Question 2 85 | Research Question 3 85 | Additional Findings 86 | Classroom Observations 87 | Summary 91 | Chapter V: CONCLUSIONS, DISCUSSIONS, AND SUGGESTIONS FOR FUTURE RESEARCH 92 | Summary of the Findings and Conclusions 93 | Summary of the Survey 93 | Finding 1 93 | Finding 2 94 | Conclusions from the Survey 95 | Finding 1 95 | Finding 2 96 | Summary of the Classroom Observations 96 | Finding 1 96 | Finding 2 97 | Finding 3 97 | Conclusions from the Classroom Observations 98 | Finding 1 98 | Finding 2 99 | Finding 3 100 | Limitations of the Study 100 | Self-Reported Survey Data 100 | Generalizability of Study 101 | County-Mandated Curriculum 101 | Recommendations for Future Research 101 | Conclusion 103 | REFERENCES 104 | APPENDIX A 121 | APPENDIX B 124 | APPENDIX C 127 | APPENDIX D 130 | APPENDIX E 132 | APPENDIX F 134 | APPENDIX G 138 |
Keywords: Discourse analysis; Lectures and lecturing; Education, Elementary; Mathematics